Hepatic fat and dietary intake as determinants of metabolic health in obese adolescents: a cross-sectional MRI study - Moran-Lev, Hadar; Sternfeld, Ron; Lazmi, Rotem; Ohayon, Rivka; Dudi, Rivka; Brener, Avivit; Sagi, Shira Zelber; Cohen, Shlomi; Lubetzky, Ronit; Gepner, Yftach (Frontiers in Nutrition, 2025)
BackgroundObesity in youth is highly associated with metabolic risk. However, a subset of individuals maintains metabolic health despite the presence of obesity. This study aims to identify key factors associated with a metabolically healthy obese (MHO) in adolescents.MethodsThis cross-sectional study included 31 adolescents with obesity [median age: 14 y, median body mass index (BMI) Z-score: 2.58] categorized as MHO or metabolically unhealthy obese (MUO) based on the presence of one or more metabolic syndrome criteria. A comprehensive evaluation included MRI assessments of abdominal adipose tissue distribution and hepatic fat content (HFC), physiological and metabolic assessment, serum biomarkers, prenatal and sociodemographic characteristics, and dietary habits.ResultsCompared to the MUO, MHO individuals exhibited significantly lower HFC (p = 0.01), liver enzymes (p = 0.004), and experienced a lower risk of complications during birth (p = 0.03). Additionally, MHO participants had significantly lower intake of total calories (p = 0.04), animal protein (p = 0.005), red meat (p = 0.02), sodium (p = 0.027), palmitic acid (p = 0.04), stearic acid (p = 0.029), arachidonic acid (p = 0.005) and calories from ultra-processed grains (p = 0.049) compared to their MUO counterparts.ConclusionAdolescents with MHO show lower hepatic fat, improved liver markers, and healthier dietary patterns than MUO peers. These findings underscore the potential influence of prenatal and lifestyle factors in distinguishing metabolic health profiles in adolescents with obesity.Clinical trial registrationhttps://clinicaltrails.gov/study/NCT06032312; NCT06032312.